Rethinking the paradox of redistribution: how private insurance and means testing can lead to universalizing reform - Margarita Gelepithis (London School of Economics and Political Science (LSE), European Institute, 2016)
Market-heavy welfare systems, in which low or moderate state benefits are topped up by private welfare arrangements, are expected to undermine political support for the extension of social rights and perpetuate benefit fragmentation over time. And where low state benefits are means-tested, political support is expected to be particularly prone to erosion. In this paper I develop the argument that the combination of private pension insurance and means-testing does not always perpetuate fragmentation. Rather, it structures the policy preferences of pension industry representatives and right-of-centre parties such that these actors push for reforms to make the state pension more universal. I make my argument by examining the reform history of nine market-heavy pension systems in the three decades since 1980. A fuzzy- set Qualitative Comparative Analysis (fsQCA) maps the conditions under which universalizing reforms have occurred, and two case studies link institutional conditions to reform outcomes via the policy preferences of key political actors.
Keywords: 330; universalism; dualization; means-testing; private insurance; pension reform